PERFORMANCE OF THE PHYSIOTHERAPIST IN A PEDIATRIC ICU - Paulo Silva Felipe Rocha, João (Health and Society, 2023)
Introduction: Physiotherapy was recognized as a profession through Decree Law nº 938, in 1969. In general, it covers patient treatment with a focus on the prevention or treatment of functional kinetic injuries caused by trauma and/or disease. Currently, in Brazil, physiotherapists are part of the multidisciplinary teams required in Intensive Care Units - ICUs, including Pediatric ICUs. Objective: To describe the areas of activity of the Physical Therapist in Pediatric Intensive Care Units – PICUs. Method: The work was developed from bibliographic research, of the descriptive and exploratory type, carried out from research bases, such as LILACS platforms - Latin American and Caribbean Literature in Health Sciences, SCIELO - Scientific Electronic Library and PubMed , websites and archives of the Ministry of Health (MS) and the Brazilian Society of Pediatrics (SBP), magazines, books and periodicals. Conclusion: Based on this research, it was possible to summarize that physiotherapy as a specialty brings a series of benefits, in the short, medium and long term, to patients hospitalized in ICUs, and especially in Pediatric ICUs, which has increasingly required professionals to, both in the search for knowledge and adaptation on a case-by-case basis, in order to avoid complications in the recovery and development of hospitalized children. During their work, physiotherapists perform multiple therapeutic approaches at different stages of treatment, seeking to avoid possible respiratory and motor complications, with the aim of providing patients with good prognosis until hospital discharge. Due to its importance for the operation of PICUs, as well as for the success of the patients’ recovery process, constant investment is needed in studies and regulations regarding the techniques and procedures performed in hospital environments.